Factors Affecting the Performance Marketing of Indonesian Farms Business in Entrepreneur Orientation - Pratama, Dimas Dipa; Santoso, Adi; Wahyuningsih, Dwi Warni (Almana : Jurnal Manajemen dan Bisnis, 2024)
Therefore, businesses person in the livestock sector, must be able to adapt to changes that exist with the application of social media in marketing the products they sell. This study aims to determine the effect of entrepreneurial competence, market orientation, and social media marketing on the marketing performance of livestock businesses. The population of this research is livestock business actors in East Java. The number of samples used was 300 livestock business actors taken randomly using a simple random sampling technique. The data that has been collected is then entered into the AMOS 24 software using the Structural Equation Modeling (SEM) analysis method to be used later to test the measurement model and the research hypothesis. The results of this study indicate that only entrepreneur competency affects marketing performance, while market orientation and social media marketing do not affect marketing performance in the livestock business.